EFFORT: energy‐efficient opportunistic routing technology in wireless sensor networks. Issue 8 (30th May 2011) - Hung, Michael Chien‐Chun; Lin, Kate Ching‐Ju; Chou, Cheng‐Fu; Hsu, Chih‐Cheng
ABSTRACT: The utilization of limited energy in wireless sensor networks (WSNs) is the critical concern, whereas the effectiveness of routing mechanisms substantially influence energy usage. We notice that two common issues in existing specific routing schemes for WSNs are that (i) a path may traverse through a specific set of sensors, draining out their energy quickly and (ii) packet retransmissions over unreliable links may consume energy significantly. In this paper, we develop an energy‐efficient routing scheme (called EFFORT) to maximize the amount of data gathered in WSNs before the end of network lifetime. By exploiting two natural advantages of opportunistic routing, that is, the path diversity and the improvement of transmission reliability, we propose a new metric that enables each sensor to determine a suitable set of forwarders as well as their relay priorities. We then present EFFORT, a routing protocol that utilizes energy efficiently and prolongs network lifetime based on the proposed routing metric. Simulation results show that EFFORT significantly outperforms other routing protocols. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : Energy‐efficiency is the key concern in wireless sensor networks (WSNs), where routing performance substantially influences energy usage. Most existing routing schemes in WSNs either utilize the best routing path every time based on certain metric for a given transmission pair, or traverse the specific set of nodes statically throughout the transmission, draining out the critical nodes' energy quickly while the energy of others are rarely consumed. In this work, we propose an energy‐efficient opportunistic routing technology (EFFORT) to utilize path diversity in order to improve energy efficiency in WSNs.